RESTITUTION RIGHT FOR VICTIMS OF SEXUAL VIOLENCE - Rahayu, Puji; Adriano; Pramono, Budi (International Peneliti Ekonomi, Sosial dan Teknologi, 2024)
The legal protection for victims of sexual violence has been addressed in statutory regulations, but its implementation remains inadequate. This is evident in the lack of competence and training among law enforcers in handling victims of sexual violence, as well as the absence of psychologists/psychiatrists who can provide assistance in explaining mental conditions. The objective of this study is to examine the legal safeguards available to victims of sexual assault crimes and evaluate the compensation options provided to these victims. This study was conducted utilizing a normative juridical research methodology, which specifically involves analyzing the implementation of legal laws or norms. This research employs both a statutory approach and a conceptual approach. The government has not adequately fulfilled its responsibilities in providing the necessary facilities and equipment to handle, protect, and support victims of sexual abuse. Statutory regulations have established compensation in the form of restitution, but the victim must still take initiative by submitting a request to secure the right to reparation. Restitution should be mandatory for the perpetrator/defendant to compensate the victim, irrespective of whether the victim initiates a request or not.